Steganograficzne metody ochrony informacji w Internecie - Duda, Anna; Galewski, Tomasz (Steganographical Methods of Protecting Data in Internet, 2005)
This article presents one the data protection methods used in companies - steganography. At the beginning there is a short presentation of the history of hiding information. The next part of the article shows some techniques which might be use in steganography. These are: text files, audio files, TCP/IP header, and the most popular - graphic. It turns out, that the best solution to protect company’s data is combining steganography and cryptography. There is a low probability of detecting and encoding hidden information. In the end of the article there is a short description of steganography applications.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1089, s. 71-82